Impresionistik dalam Kritik Sastra Arab Masa Jahiliah - Annisa Khairunnisa; Tatik Mariyatut Tasnimah; Moh. Wakhid Hidayat; Arif Rahmatul Aji (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The purpose of this study is to reveal the distinctive impressionistic characteristics of the Jahiliah period. Because it is relevant to current critical methods, impressionistic also exists in the assessment of Arabic literary works, but it is different and tends to be rejected. Therefore, this study needs to be examined so that it can serve as a practical reference. This study uses a descriptive qualitative design with a historical approach. The data for this study consists of information and facts that discuss impressionistic in Jahiliah-era criticism. The data sources are books by literary critics, scientific journals, and relevant studies. The data collection stage involves careful reading and listening. The data is then collected by recording the content. The analysis stage involved content analysis, interpretation, and conclusion. The research findings indicate that the fundamental character of literary criticism during the Jahiliah period was impressionistic. This is reflected in the concept of natural feeling (spontaneity), based on effectiveness, and the absence of standard references in criticism. However, the impressionistic character of the Jahiliah period had its distinctiveness. This is demonstrated by the credibility of Jahiliah-era critics, who possess knowledge, intuition, and experience; the natural ability of poets to express poetic diction; and the esteemed status of Arab literary works from that period. Although their criticism is brief and spontaneous, the authors, poets, and poems are seamlessly integrated into a credible and intuitive understanding. This is due to their habit of composing poetry and their strong emotional attachment to it. The theoretical implications of this research can offer new insights into the exploration of innovative methods in Arabic literary criticism. Practically, it can serve as a reference for current impressionistic criticism methods to be more widely accepted, as it refers to new standards of integrity and quality. Abstrak Tujuan penelitian ini adalah menyingkap karakter impresionistik yang khas pada masa Jahiliah. Sebab relevan dengan metode kritik saat ini, dalam penilaian karya sastra Arab juga terdapat impresionistik, namun berbeda dan cenderung tertolak. Oleh karena itu, penelitian ini perlu dikaji untuk dapat menjadi acuan praktis. Penelitian ini menggunakan desain kualitatif deskriptif dengan pendekatan historis. Data kajian ini ialah informasi dan fakta yang mengulas impresionistik dalam kritik masa Jahiliah yang bersumber dari buku kritikus sastra, jurnal ilmiah, dan kajian yang relevan. Data dikumpulkan dengan metode simak dan mencatat konten data dan dianalisis dengan analisis isi, interpretasi, dan konklusi. Hasil penelitian menunjukkan bahwa karakter kritik sastra masa Jahiiliah secara mendasar memuat kritik impresionistik. Hal ini terkover dalam konsep rasa alamiah (spontan), berdasarkan kepada keberkesanan, dan tidak memiliki acuan baku dalam mengkritik. Akan tetapi, karakter impresionistik masa Jahiliah memiliki kekhasan. Ini ditunjukkan dengan kualitas kritikus masa Jahiliah lebih kredibel dengan pengetahuan, intuisi, dan pengalamannya; pengetahuan penyair yang alamiah mengutarakan diksi-diksi puisi; dan karya sastra Arab masa itu dinilai mulia. Walaupun kritikannya singkat dan spontan, namun pengarang, penyair, dan puisi telah terintegrasi dalam pemahaman naluriah yang kredibel. Hal ini dilandasi oleh kebiasaan mereka dalam berpuisi dan sentimentalnya yang kuat terhadap puisi. Implikasi penelitian ini secara teoretis dapat memberikan khazanah baru dalam eksplorasi metode kritik sastra Arab yang khas. Adapun secara praktis dapat menjadi acuan metode kritik impresionistik saat ini agar lebih diterima, sebab merujuk standar baru yang berintegritas dan berkualitas.